Practicum Supervisors'Insights Regarding Non-Native Teachers in Training - Enric Llurda (Universitas Katolik Indonesia Atma Jaya, 2013)
This paper presents the results of a series of oral interviews withpracticum supervisors in MA TESOL programs, regarding theirviews on the characteristics and the challenges experienced by nonnativeteachers in training while they were doing their practice teaching. Practicum supervisors constitute a group of professionals with a unique and privialged perspective onto the classroom performance of both native and non-native student teachers and through these interviews they can express their concerns and appreciations of non-native students teachers in North-American TESOL Programs Keywords: practicum supervisor; non-native teachers, TESOL Programs